2005
DOI: 10.1002/qua.20439
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Cr and V in FeAl B2 phase

Abstract: Ab initio calculations of the properties of the FeAl B2 phase alloyed by Cr or V are performed on the basis of the full potential augmented plane-wave (APW) ϩ local orbitals (lo) method. The site preference occupation for Cr and V atoms in this compound is investigated. We studied the changes in the site preference for Cr and V substituting for Fe or Al when the vacancy on the Fe site is formed. Existence of the vacancy significantly changes the site occupation preference for Cr that transits from the Al site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This analysis was based on a comparison of the mixing energies following the scheme presented in previous work. [20] It was also reported that Cr and V occupy the Al site in the ideal Fe-Al B2 phase. In the case of a vacancy on the Fe site in Fe-Al, V occupies the Al site and Cr occupies the Fe site nearest to the vacancy.…”
Section: The Preference Of Site Occupation Of the Alloying Elementsmentioning
confidence: 95%
See 2 more Smart Citations
“…This analysis was based on a comparison of the mixing energies following the scheme presented in previous work. [20] It was also reported that Cr and V occupy the Al site in the ideal Fe-Al B2 phase. In the case of a vacancy on the Fe site in Fe-Al, V occupies the Al site and Cr occupies the Fe site nearest to the vacancy.…”
Section: The Preference Of Site Occupation Of the Alloying Elementsmentioning
confidence: 95%
“…The vacancies in the Fe-Al B2 phase are formed mainly on the Fe sublattice [20] ; therefore, it is of interest to check the influence of the alloying transition metal (TM) on the preference site for the vacancy formation. The calculated results are summarized in Table 2.…”
Section: Energy Of Vacancy Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Density Functional Theory (DFT) has been applied [29][30][31][32][33][34][35], and the mixing energy for the Ni 12 P 5 + Li system has been calculated as well as the spatial distribution of differential electron density (DED) and the Density of States (DOS) for the system. The software package WIEN2k-09.2 [36] was used for the electronic structure calculations.…”
Section: Metallic Nanowires In Crystal Channels (Li In Ni 12 P 5 )mentioning
confidence: 99%
“…Presence of these defects in FeAl has significant influence on the material properties stimulating the research aimed to use peculiar defect behaviour for improving material performance [3e6]. We found, in our previous works, that the vacancies exist mainly on the Fe sublattice [7] and the anti-sites are more feasible energetically on the Al sublattice [8] in FeAl B2 phase. These results are in agreement with experimental and theoretical studies [9e11].…”
Section: Introductionmentioning
confidence: 97%